Transmaxillary anchored silicon embedded gauze plug in the post‐operative treatment of a large oromaxillary fistula caused by a supernumerary cheek tooth. (7th February 2018) - Hevesi, A. T.; Uto, D.; Takacs, N.; Lorincz, V.; Simhofer, H.
Summary: A 9‐year‐old Hungarian sport horse gelding was presented to the clinic in poor condition displaying malodorous bilateral purulent nasal discharge. Oral examination revealed the presence of supernumerary 111 and 211. Bilateral diastema formation between the third maxillary molars and the supernumerary teeth with deep periodontal pockets and massive food impactions were diagnosed endoscopically. Radiography revealed inhomogenous sinus opacities in the left and right paranasal sinuses. Following bilateral oral extractions of the supernumerary cheek teeth and third maxillary molars, bilateral oromaxillary fistula formations were diagnosed (about 17 mm diameter on the right side). Bilateral frontal and right‐sided maxillary trephinations and resection of the right bulla of the maxillary septum were performed. Massive food impactions of the left and right paranasal sinuses were removed under endoscopic control. Repeated trans‐endoscopic sinus lavage was performed post‐operatively. After 2.5 months, the large right‐sided oromaxillary communication was temporarily closed with a transmaxillary anchored, gauze‐cored silicon plug on an outpatient basis. Follow‐up examination after 187 days revealed complete closure of the oromaxillary fistula and absence of sinusitis. In a 1.5‐year follow‐up control, no pathological conditions were found.